Multipurpose Considerations in Watershed Management - Vajda, A DE (Journal of Soil and Water Conservation, 2022)
During the last few decades, the deniand for Mater has increased con- siderably in ahnost all countries. In large areas today the increase in water consurnption for industrial purposes is several times greater than it Meas some forty years ago, and the same can be said of town water supplies, where both the number of consumers and the per capita demand have increased considerably. Irrigation, always a heavy consumer, is steadily increasing not only in the arid and semi-arid zone, but is also spreading to areas where, though the mean annual rainfall is reasonably good, the seasonal distribution is unfavourable and supplementary irrigation is needed for safe cropping. Water power is also competing more and more for water. Though it does not actually consume water, it often requires storage of large quantities when other consumers need ’vvater for consumptive uses. The interest of flood protection is also often opposed to the interest of the other users. These competing and often contradictory interests of the various users have to be satisfied in such a way that the available water is used for the greatest possible benefit of the population of the river basin and the country as a whole. Necessarily, the river basin has become the unit for multipurpose river development planning. In general, multipurpose projects can only be effective when the river flow is fully con- trolled. Apart from a few examples where the river régime is so favourable that it does not require major corrections, multipurpose projects can only become effective when the damaging flood peaks are reduced and flood water, stored during the flood period, is utilized for useful purposes during the periods of need.